Depth of arterial supply of forehead: a meta-analysis - Mateusz Trzeciak; Tomasz Gładysz; Wojciech Przybycień; Jędrzej Bartoszcze; Julia Pisarek; Michał Mordarski; Joe Iwanaga; Mateusz Koziej; Jerzy A. Walocha (Folia Morphologica)
BACKGROUND: The rapid growth of aesthetic medicine has led to an increased demand for non-surgical cosmetic procedures in the frontal region of the face. However, alongside this rise in popularity, there has also developed a growing awareness of the potential complications associated with these procedures, especially connected with fillers. The intricate vascular anatomy of the forehead, specifically the supratrochlear (STA) and supraorbital (SOA) arteries, poses significant risks if not thoroughly understood. While the morphological course of these vessels has been well-documented and analysed, detailed knowledge about their depth remains vital for enhancing procedural safety. MATERIALS AND METHODS: Five research papers were analysed in this meta-analysis. The analyses of STA and SOA were performed in two separate places bilaterally: at the level of the glabella, and above the eyebrow. RESULTS: A total of 201 SOA arteries and 282 STA arteries were analysed at the level of the glabella and above the eyebrow. The results were as follows: 5.68 mm, 95% CI (4.58–6.78) for SOA at the glabella, 5.53 mm, 95% CI (4.79–6.28) for SOA above the eyebrow, 4.45 mm, 95% CI (3.43–5.47) for STA at the glabella, and 3.53 mm, 95% CI (3.21–3.85) for STA above the eyebrow. CONCLUSIONS: The supratrochlear artery tends to become more superficial along its path, while the supraorbital artery remains at a consistent depth across various anatomical levels. For injections in the medial part of the forehead, it is advisable to place the needle up to 2.5 mm deep or laterally to the artery’s path. In contrast, injections in the lateral part of the forehead can be administered slightly deeper, up to 3.5 mm. To minimise the risk of complications, performing a high-resolution linear ultrasonography (USG) exam prior to injection is recommended, allowing for needle placement either laterally or medially to the vessels.